Reflections on Rumi’s Mathnawi and Ecological Spirituality: Introducing an African Perspective - Fahm, AbdulGafar Olawale (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The Mathnawi, a thirteenth-century mystical poem by Jalal al-Din Rumi, is traditionally associated with Islamic spirituality, characterized by its rich imagery, metaphors, stories, and analogies. Despite its primary mystical and didactic nature, discernible elements reflecting a nature-centric worldview are evident within its verses. This article explores the extent to which ecological spirituality themes are present in the Mathnawi. Employing a qualitative analysis approach, it investigates how Rumi and his work are integrated into contemporary conversations surrounding ecological concerns, with a specific lens on Nigeria. Drawing from practical examples, the study explores the portrayal and utilization of Rumi’s insights within the context of Nigeria’s ecological landscape. Furthermore, it incorporates reflections on insights gleaned from indigenous Nigerian philosophical and cultural traditions, enriching the discourse on ecological spirituality. The inquiry contemplates the potential for incorporating perspectives from other African cultures and Islamic scholars into this dialogue. Ultimately, the analysis suggests that embracing an African perspective can deepen and broaden Rumi’s ecological conceptualizations of the universe, offering new insights and avenues for understanding and addressing contemporary ecological challenges.